Bioconversion of Palm Kernel Cake (PKC) to value added feed using fibrolytic bacteria and fungi - Clemente Michael Wong Vui Ling; Elaine Remi Douglas; Sharon Lau Yu Ling (2009)
The inclusion of PKC in poultry diet is limited due to the presence of several antinutritive materials in PKC such as galactomannan and xylan. These anti-nutritive materials increase the viscosity of the diet due to their high absorbability of water and therefore inhibit the absorption of nutrients by the animals. One way to overcome this problem is to treat PKC with enzyme or enzyme-producing microorganisms to digest those recalcitrant components. Hence, this work was carried out to isolate microorganisms; especially bacteria and fungi with fibrolytic activities such as galactomannanase, xylanase and endoglucanase which can be used to treat PKC.